Molecular modeling of non-covalent binding of Ligustrum lucidum secoiridoid glucosides to AP-1/matrix metalloproteinase pathway components - Pathomwat Wongrattanakamon (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Ligustrum lucidum secoiridoid glucosides have been demonstrated to treat various types of diseases such as inflammation, pain, hepatotoxicity and hyperlipidermic as well as tonic for liver and kidney. Matrix metalloproteinases (MMPs) play a key role upon the pathology of photoaging. The present computational study showed that among the six secoiridoid glucosides (ligustroside, lucidumoside A, lucidumoside C, neonuezhenide, oleoside dimethylester, and oleuropein), ligustroside and lucidumoside A competitively inhibit all MMP-1, MMP-3, and MMP-9 activities in the docking models. The molecular docking analysis revealed a network of interactions between MMP-1, MMP-3, and MMP-9 and the ligands; ligustroside and lucidumoside A, and oxygen-containing and hydrophobic functional groups appear to be responsible for these enhanced interactions. The effect of ligustroside and lucidumoside A on the transcription factor AP-1 action was also investigated using molecular docking and dynamics simulations. The experiments suggested that inhibition of an AP-1–DNA complex formation could be on account of the direct interference of AP-1 binding onto the DNA binding sequence by ligustroside and lucidumoside A. The results suggest that both compounds have the highest potential for application as an anti-aging agent with the MMP inhibitory and anti-transcriptional activities.